PENERAPAN MODEL PEMBELAJARAN INKUIRI SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR IPS KELAS 4 SD - Fahrurrozi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the differences in social science learning outcomes for fourth-grade elementary school students by applying the inquiry learning model. The type of research used was a literature review, which was obtained from the research that has been conducted previously. Data collection was carried out by browsing journals through Google Scholar and Sinta. Based on the application of inquiry, it was selected 10 research outcomes to be analyzed. The average value before applying the inquiry learning model was achieved at 64.96. After applying the inquiry learning model, the students’ learning outcomes increased to 85.85. It can be said that learning with the inquiry model could improve social science learning outcomes for fourth-grade students.